The effect of psychodrama application on nursing students' problem-solving skills - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2014)
Objective: The aim of this study is to determine the effects of the psychodrama in improving problem solving skills. Methods: A quasi-experimental and single group pretest-posttest study design is utilized. The sample of the study consists of the senior baccalaureate nursing students of Marmara University College of Nursing (n=10) who volunteered after the explanation of what psychodrama is and whose schedules fit the psychodrama group date and time. Psychodrama sessions were arranged as three hour in each week and made in total 21 psychodrama sessions. Data were collected questionnaire form, group evaluation forms and problem solving scale. The participants filled in the problem solving scale before group sessions, during the last session and after one year via e-mail. Statistical methods and feedbacks from students were used while evaluating the findings. Results: The scores of the participants on the problem solving scale during the periods of pre-group, post-group and one year after the group was statistically significant. Students stated that they achieved progress in self-awareness, self-evaluation, creativity, empathy, problem solving and expressing their emotions. Discussion: In this study both the statistical data and the participants. feedbacks showed that psychodrama method was effective. In the light of these findings, psychodrama method is suggested to be used in nursing training.
Keywords: psychodrama; problem solving skills; nursing students